The paralytic shellfish toxin effect on bioenergetic constituents of the fishery resource Chorus giganteus (Gastropoda: Muricidae). (September 2022) - Andrade-Villagrán, P.V.; Agüero, M.J.; Navarro, J.M.; Urzúa, Á.
Abstract: Alexandrium catenella, one of the most common harmful microalgae observed in southern Chile, produces paralytic shellfish toxins, which can affect many organisms throughout the trophic chain. This research evaluated how paralytic shellfish toxins affected the principal bioenergetic constituents and fatty acids composition of the carnivorous snail Chorus giganteus . Snails were separated into a "toxic" group that was fed the toxic clam Mulinia edulis (which was previously fed A. catenella ), and a "non-toxic" group, fed non-toxic clams. Both groups were kept under these conditions for 63 days. Our results indicated no difference in the ingestion rate of toxic versus non-toxic snails; however, a higher protein level was identified in toxic snails. The total lipid content proved to be no different in toxic versus non-toxic snails; although, an effect of the toxic diet on the fatty acid profile of C. giganteus was observed. High levels of essential polyunsaturated fatty acids, especially docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) in toxic snails, were identified. Our results suggest that exposure to paralytic shellfish toxins, through diet, may cause changes in the biochemical composition of C. giganteus, which may have a subsequent impact on its energetic physiology. Highlights: PST ingestion does not affected the ingestion rate or total lipids in C. giganteus . Ingestion of PST increased the total proteins and the total PUFAs in C. giganteus . PST ingestion caused changes in the fatty acid profile of Chorus giganteus .